Tauhid Education Concept by Sheikh Abdurrahman Bin Nȃsir Al-Sa'di (Study of Book of Taisȋr Al-Karȋm Al-Rahmȃn Fi Tafsȋr Kalȃmi Al-Mannȃn) - Nurul Yaqin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The concept of tauhid education by syeikh abdurrahman bin nȃsir al-sa’di that the study of kitab taisȋr al-karȋm al-rahmȃn fi tafsȋr kalȃmi al-mannȃn. Thesis of Islamic education study program, postgraduate program in Muhammadiyah University of Surabaya. This research was motivated by many differences in understanding of tawhid and its educational concept, even though tawhid is fardhu 'ain, the principle of development and solutions to life's problems. The research questions were formulated: 1) How does sheik Abdurrahman bin Nȃsir al-Sa'di understand the Tauhid verses in the book Taisȋr al-karȋm al-Rahmȃn? 2). What is the concept of tauhid education according to Sheikh Abdurrahman   al-Sa'di in the book Taisȋr al-karȋm al-Rahmȃn? 3). How is the relevance of the concept of tauhid education according to Sheikh Abdurrahman al-Sa'di in Indonesian territory? This thesis used purely library research with the type of qualitative research. The results of the study concluded that Shaykh al-Sa'di believed: The Tauhid of the apostles were the determination of the oneness of Allah on His names, attributes, deeds and rights. The concept of education determined that the Prophet Muhammad was an educator, a successful role model and best of all times. The purpose of education realized the servitude only to Allah SWT as the purpose for which humans were created. The learning methods used in delivering monotheistic education were exemplary methods, soul cultivation, thinking and habituation of good deeds. The relevance of the concept of education in Indonesia was as follows: a. Aim to build a whole human being physically and mentally. This was also the core aim of education in general in Indonesia, b. Aspiring to prosper the region so that Allah SWT can give His blessings from heaven and earth, c. Developing a healthy mental and character from an early age is oriented towards seeking the pleasure of Allah in all areas of life. Furthermore, this was the application and hope of the Indonesian people in general.